Public Relations Strategies for Promoting the Modernization of Smart Ambulance Facilities at PT. Ambulance Pintar Indonesia - Mohamad Alfian Yusuf Nurrahman; Khaerudin Imawan; Welly Wihayati (Jurnal Bisnis dan Komunikasi Digital, 2026)
Modernization of ambulance facilities is very important in elevating the standard of medical care services as well as fostering confidence among service providers among the community. PT. Ambulance Pintar Indonesia continuously invests in updating its facilities, requiring a suitable public relation strategy to market them. Therefore, the current research study seeks to assess the public relation strategy utilized in promoting ambulance facility modernization and determine the facilitating and hindering aspects. Qualitative methodology with descriptive techniques was used for the current research. The data collected were gathered from in-depth interviews conducted with the branch managers, PR staff, and consumers as well as other relevant documents. The outcome is that the implementation of the public relations strategy was made following the steps of fact-finding, planning, communication, and action, as well as evaluation. The strategy has been implemented using social media tools, the company's website, and involvement in health exhibitions, emphasizing visualization of modernization and regulation. The success of the strategy has been defined by the increase in consumer trust, positive public reaction, and sales growth. Supporting factors included the tangible quality of modernization and regulatory legitimacy, while inhibiting factors related to differences in audience understanding of medical technical terms. Overall, the implemented public relations strategy strengthened the company's professional image and positioning in the ambulance provider industry.